4(x-8)+12=7(x-3)-3x

Simple and best practice solution for 4(x-8)+12=7(x-3)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-8)+12=7(x-3)-3x equation:



4(x-8)+12=7(x-3)-3x
We move all terms to the left:
4(x-8)+12-(7(x-3)-3x)=0
We multiply parentheses
4x-(7(x-3)-3x)-32+12=0
We calculate terms in parentheses: -(7(x-3)-3x), so:
7(x-3)-3x
We add all the numbers together, and all the variables
-3x+7(x-3)
We multiply parentheses
-3x+7x-21
We add all the numbers together, and all the variables
4x-21
Back to the equation:
-(4x-21)
We add all the numbers together, and all the variables
4x-(4x-21)-20=0
We get rid of parentheses
4x-4x+21-20=0
We add all the numbers together, and all the variables
1!=0
There is no solution for this equation

See similar equations:

| 20-4n=5n+n | | -x+1.8=11.9 | | 8+3x=4x+1 | | 2x+4.5=x+10.5 | | y=51=12 | | 160+3x=195x-2x | | 7a-4=3(a+9)4a | | 1/7x+5=12 | | ,y=51=12 | | 6x-1=7(x-3) | | 9x-5+2x+13+7x+5=180 | | 3a+7.9+4.5a-5.3a=-0.59+2.6 | | 3p-7=7p+23 | | 2m-3.6=-7.6 | | -16+4x=-40-2x | | 14x+14=-18 | | 5x+3.4=2x+43 | | -4x+8=2(x+6) | | Y=0x+10/13 | | 62+x=x | | 2x-3(x-4)=8 | | 8-7/10c=6+1/5c | | x+x+56+77=180 | | 6p+15=7p+9+3 | | 62+63=x | | 9x+19=5x-7 | | 140/112=x/112 | | f2,000=75+0.2(2,000) | | 120+90+m=180 | | 6p+15=7p+93 | | 2x-9=8x-3 | | 1/2(10x+8)-2x=7x+8 |

Equations solver categories